Notes and problems in applied general equilibrium economics - Dixon, Peter B. (Advanced textbooks in economics, 1992)
"General-equilibrium" refers to an analytical approach which looks at the economy as a complete system of inter-dependent components (industries, households, investors, governments, importers and exporters). "Applied" means that the primary interest is in systems that can be used to provide quantitative analysis of economic policy problems in particular countries. Reflecting the authors' belief in the models as vehicles for practical policy analysis, a considerable amount of material on data and solution techniques as well as on theoretical structures has been included. The sequence of chapters follows what is seen as the historical development of the subject. The book is directed at graduate students and professional economists who may have an interest in constructing or applying general equilibrium models. The exercises and readings in the book provide a comprehensive introduction to applied general equilibrium modeling. To enable the reader to acquire hands-on experience with computer implementations of the models which are described in the book, a companion set of diskettes is available